A Randomized, Endoscopist-Blinded, Prospective Trial to Compare the Efficacy and Patient Tolerability between Bowel Preparation Protocols Using Sodium Picosulfate Magnesium Citrate and Polyethylene-Glycol (1 L and 2 L) for Colonoscopy. (3rd March 2020) - Kim, Sang Hoon; Kim, Ji Hyeong; Keum, Bora; Jeon, Han Jo; Jang, Se Hyun; Choi, Seong Ji; Kim, Seung Han; Lee, Jae Min; Choi, Hyuk Soon; Kim, Eun Sun; Jeen, Yoon Tae; Lee, Hong Sik; et al.
Abstract : Patient compliance during bowel preparation is important for successful colonoscopy. Bowel preparation with polyethylene glycol (PEG), the most commonly used solution for cleansing, involves the unpleasant ingestion of a large amount of liquid. Sodium picosulfate magnesium citrate (SP-MC) solution is an alternative option with better palatability than PEG. Therefore, in this study, we compared the efficacy and patient tolerability among the following three bowel preparation protocols: 2 L PEG-ascorbic acid (ASc), 1 L PEG-ASc plus bisacodyl, and SP-MC 340 mL plus bisacodyl. We conducted a randomized prospective endoscopist-blinded study between August 2018 and January 2019. A total of 311 patients were randomly classified into three groups according to the above-described bowel preparation protocols. To evaluate the efficacy of bowel cleansing, we used the Boston Bowel Preparation Scale. The degree of symptoms and the patients' satisfaction with each bowel preparation method were investigated using a questionnaire completed before sedation for colonoscopy. The baseline characteristics were similar among the three groups. There was no significant difference in the bowel preparation quality among the three groups. However, the incidence of symptoms, such as abdominal fullness and pain, was significantly lower (P = 0.006 and 0.027, respectively) while the patients' satisfaction rate was significantly higher (P = 0.012 ) in the SP-MC plus bisacodyl group than in the two PEG groups. In this study, the efficacy of the SP-MC plus bisacodyl solution was similar to that of the PEG solutions. However, patient tolerability and satisfaction were better in the SP-MC plus bisacodyl group than in the other groups. In conclusion, the use of SP-MC plus bisacodyl bowel preparation solution might be a better method for providing good intestinal cleansing and improving patient compliance.